2022
DOI: 10.3346/jkms.2022.37.e353
|View full text |Cite
|
Sign up to set email alerts
|

How We Have Treated Severe to Critically Ill Patients With Coronavirus Disease 2019 in Korea

Abstract: Since 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread worldwide, and the coronavirus disease 2019 (COVID-19) pandemic currently continues. In response to this unprecedented pandemic, several researchers and medical staff have struggled to find appropriate treatments for COVID-19. Patients with mild symptoms can recuperate with symptomatic care, however establishing treatment for severe to critically ill patients who can have a high mortality has been essential. Accordingly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…As the treatment guidelines for COVID-19 have been revised and several treatment options, including antiviral agents, immunomodulatory agents, and anticoagulants, have been well established, 17 18 19 20 it was expected that the use of antibiotics would decrease over time. However, there were no significant changes in antibiotic use over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…As the treatment guidelines for COVID-19 have been revised and several treatment options, including antiviral agents, immunomodulatory agents, and anticoagulants, have been well established, 17 18 19 20 it was expected that the use of antibiotics would decrease over time. However, there were no significant changes in antibiotic use over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that short-term neurological outcome was favourable in 65% (ref. 1,2,5 ), patients with good neurological recovery, 29% (ref. 1,2,5 ) had respiratory failure, 23% (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic symptoms are present in about 57% (ref. 1 ) of patients with COVID-19 and include hyposmia, parosmia, dysgeusia, myalgias and headache, which appear at an early stage of the disease [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…43 44 45 In Korea, various immunomodulators, including baricitinib, were administered to patients requiring supplemental oxygen. 47 Dosage modifications are recommended for patients with renal or hepatic impairment. 43 Olumiant is not recommended for patients with an absolute lymphocyte count less than 200 cells/µL or an ANC less than 500 cells/µL.…”
Section: Part 1 Approved Covid-19 Therapeuticsmentioning
confidence: 99%